Synthesis of Bimetallic Conductive 2D Metal–Organic Framework (CoxNiy‐CAT) and Its Mass Production: Enhanced Electrochemical Oxygen Reduction Activity. Issue 17 (1st April 2019) - Yoon, Hajin; Lee, Sujeong; Oh, Sojin; Park, Heejun; Choi, Sora; Oh, Moonhyun
Abstract: The development of new electrocatalysts for electrochemical oxygen reduction to replace expensive and rare platinum‐based catalysts is an important issue in energy storage and conversion research. In this context, conductive and porous metal–organic frameworks (MOFs) are considered promising materials for the oxygen reduction reaction (ORR) due to not only their high surface area and well‐developed pores but also versatile structural features and chemical compositions. Herein, the preparation of bimetallic conductive 2D MOFs (Cox Niy ‐CATs) are reported for use as catalysts in the ORR. The ratio of the two metal ions (Co 2+ and Ni 2+ ) in the bimetallic Co x Ni y ‐CATs is rationally controlled to determine the optimal composition of Co x Ni y ‐CAT for efficient performance in the ORR. Indeed, bimetallic MOFs display enhanced ORR activity compared to their monometallic counterparts (Co‐CAT or Ni‐CAT). During the ORR, bimetallic Co x Ni y ‐CATs retain an advantageous characteristic of Co‐CAT in relation to its high diffusion‐limiting current density, as well as a key advantage of Ni‐CAT in relation to its high onset potential. Moreover, the ORR‐active bimetallic Co x Ni y ‐CAT with excellent ORR activity is prepared at a large scale via a convenient method using a ball‐mill reactor. Abstract : Bimetallic conductive 2D MOFs of Co x Ni y ‐CAT with varied ratios of Co 2+ and Ni 2+ are successfully synthesized and display enhanced oxygen reduction reaction (ORR) activities compared to monometallic counterparts, Co‐CAT and Ni‐CAT. In addition, mass production of ORR‐active Co x Ni y ‐CAT was demonstrated using a ball‐mill reactor.